On the role of operational dynamics in biogeochemical efficiency of a soil aquifer treatment system - S. Ben Moshe; N. Weisbrod; F. Barquero; J. Sallwey; O. Orgad; A. Furman (Hydrology and Earth System Sciences, 2020)
Sustainable irrigation with treated wastewater (TWW) is a promising solution for water scarcity in arid and semi-arid regions. Soil aquifer treatment (SAT) provides a solution for both the need for tertiary treatment and seasonal storage of wastewater. Stresses over land use and the need to control the obtained water quality makes the optimization of SAT of great importance. This study looks into the influence of SAT systems' operational dynamics (i.e., flooding and drying periods) as well as some aspects of the inflow biochemical composition on their biogeochemical state and the ultimate outflow quality. A series of four long-column experiments was conducted, aiming to examine the effect of different flooding/drying period ratios on dissolved oxygen (DO) concentrations, oxidation–reduction potential (ORP) and outflow composition. Flooding periods were kept constant at 60 min for all experiments while drying periods (DPs) were 2.5 and 4 times the duration of the flooding periods. Our results show that the longer DPs had a significant advantage over the shorter periods in terms of DO concentrations and ORP in the upper parts of the column as well as in the deeper parts, which indicates that larger volumes of the profile were able to maintain aerobic conditions. DO concentrations in the deeper parts of the column stabilized at ∼3–4 mg L−1 for the longer DPs compared to ∼1–2 mg L−1 for the shorter DPs. This advantage was also evident in outflow composition that showed significantly lower concentrations of <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="68d940fa21d9c6691de36bd82f3e56d8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="hess-24-417-2020-ie00001.svg" width="24pt" height="15pt" src="hess-24-417-2020-ie00001.png"/></svg:svg>-N, dissolved organic carbon (DOC) and total Kjeldahl nitrogen (TKN) for the longer DPs (∼0.03, ∼1.65 and ∼0.62 mg L−1 respectively) compared to the shorter DPs (∼0.5, ∼4.4 and ∼3.8 mg L−1, respectively). Comparing experimental ORP values in response to different DPs to field measurements obtained in one of the SAT ponds of the SHAFDAN, Israel, we found that despite the large-scale differences between the experimental 1-D system and the field 3-D conditions, ORP trends in response to changes in DP, qualitatively match. We conclude that longer DP not only ensure oxidizing conditions close to the surface, but also enlarge the active (oxidizing) region of the SAT. While those results still need to be verified at full scale, they suggest that SAT can be treated as a pseudo-reactor that to a great extent could be manipulated hydraulically to achieve the desired water quality while increasing the recharge volumes.